Small-molecule STAT3 Signaling Pathway Modulators from Polygonum cuspidatum - Liu, Jiawei; Zhang, Qing; Chen, Kaotang; Liu, Jingli; Kuang, Shan; Chen, Weiwen; Yu, Qiang (Planta Medica, 2012)
Constitutively activated STAT3 plays a pivotal role in oncogenesis and metastasis in many human cancers, and STAT3 has been validated as a novel anticancer drug target. Thus, the identification of small molecules that modulate STAT3 activity could be of great therapeutic importance. The aim of this study was to isolate novel modulators of the STAT3 signaling pathway from the roots of Polygonum cuspidatum by bioassay-guided fractionation using a STAT3 reporter gene assay. 2-Methoxystypandrone (1), as well as three anthraquinones (2–4), were identified as major active components of P. cuspidatum. Compound 1 demonstrated a potent inhibitory effect on STAT3 activation and significantly inhibited cell proliferation of human breast cancer cells, especially those with constitutively activated STAT3 (IC50 = 2.7–3.1 µM). The SAR analysis of quinone analogues suggested that the phenolic and carbonyl groups are the key structures contributing to their inhibitory activities against the STAT3 signaling.
Keywords: Polygonum cuspidatum; Polygonaceae; STAT3 signaling; modulators; 2-methoxystypandrone